ETNOGRAFI BUKA GILING: RITUS INDUSTRI DAN SISTEM SOSIAL DI PABRIK GULA LESTARI PATIANROWO - I'in Dwi Susanti; Suwardi Endraswara; Sri Harti Widyastuti (Universitas Sebelas Maret, 2026)
The buka giling ritual (sugarcane milling season opening) at Lestari Sugar Factory, Patianrowo, is more than a ceremonial marker for the production season; it represents a complex industrial rite embedded with symbolic, historical, and social significance. Amid the pressures of national sugar industry modernization, this tradition persists as both an adaptive mechanism and an integrative force between local communities and industrial institutions. This study examines how the buka giling ritual operates as a social system through symbolic and structural analysis. A qualitative research design employing an interpretive ethnographic approach was adopted. Data were gathered via participant observation, semi-structured indepth interviews with community leaders, workers, management, and sugarcane farmers, as well as documentation of ritual proceedings. Analysis followed the Miles, Huberman, and Saldaña (2014) interactive model, validated through source triangulation. The theoretical framework draws on Talcott Parsons’ (1951) AGIL social systems theory and Clifford Geertz’s (1973) interpretive cultural theory.The findings reveal that the buka giling ritual fulfills four primary social functions: (1) adaptation to industrial transformation, (2) goal attainment through collective production and solidarity, (3) social integration among diverse actors, and (4) latency through preservation of local cultural values and identity. Ritual elements such as the manten tebu procession and cethik geni ceremony symbolize the unification of nature, community, and industrial technology. This study contributes to the fields of industrial anthropology and cultural labor studies, recommending institutional support for preserving local rites as a form of productive and sustainable social integration.